2014
DOI: 10.1093/cid/ciu658
|View full text |Cite
|
Sign up to set email alerts
|

High Usage of Topical Fusidic Acid and Rapid Clonal Expansion of Fusidic Acid–Resistant Staphylococcus aureus: A Cautionary Tale

Abstract: Our aim was to assess national prescribing trends and determine longitudinal resistance patterns for topical antimicrobials in New Zealand. We observed a dramatic increase in fusidic acid (FA) resistance, and clonal expansion of FA-resistant Staphylococcus aureus. This increase was concurrent with a significant national increase in topical FA dispensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 10 publications
0
69
0
Order By: Relevance
“…The size of the nodes represents the number of isolates included in that type Patients with hand eczema in Östergötland County are rarely treated with antibiotics, systemically or locally, which is reflected in the low prevalence of resistance and resistance genes in S. aureus isolated from patients. The fusidic acid resistant t127/CC1 clone colonizing three patients in our study has previously been frequently isolated around the globe [33][34][35].…”
Section: Discussionmentioning
confidence: 69%
“…The size of the nodes represents the number of isolates included in that type Patients with hand eczema in Östergötland County are rarely treated with antibiotics, systemically or locally, which is reflected in the low prevalence of resistance and resistance genes in S. aureus isolated from patients. The fusidic acid resistant t127/CC1 clone colonizing three patients in our study has previously been frequently isolated around the globe [33][34][35].…”
Section: Discussionmentioning
confidence: 69%
“…This was also a clonal dissemination, although with a different clone than in Europe. In parallel to this clonal dissemination, a significant increase in dispensing rates for topical fusidic acid was seen in New Zealand (Williamson et al 2014). The correlation between previous topical use of fusidic acid and resistance in S. aureus has previously been shown in dermatology patients (Heng et al 2013).…”
Section: Fusidic Acid Resistancementioning
confidence: 80%
“…Previous study has demonstrated that these spa types correspond to multilocus sequence type 5 (ST5) and ST1, respectively, and that both of these clones in NZ (ie, t002 ST5 MRSA and t127 ST1 MSSA) are generally resistant to fusidic acid. 16 Interestingly, of the 142 children who had concurrent nasal and oropharyngeal colonization in 2013, 57 children (40.1%) had discordant isolates on the basis of spa typing. …”
Section: Molecular Typing and Discordance Between Nasal And Oropharynmentioning
confidence: 99%